LENGTH WEIGHT RELATIONSHIP OF NILE TILAPIA OF OREOCHROMIS NILOTICUS NILOTICUS (LINNAEUS, 1758 ) ( FAMILY : CICHLIDAE ) - K. Karal Marx; T. Vaitheeswaran; P. Chidambaram; S. Sankarram; P. Karthiga (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Length-Weight relationship was studied in Oreochromis niloticus niloticus, for a period of nine months from September 2012 to May 2013. The slope value (b) estimated for O. niloticus niloticus of both sexes was found to be 2.3133. The regression equations calculated for female was Log W = -3.4168 + 2.3133 Log L. The correlations coefficient was found to be significant (P